2004
DOI: 10.1111/j.0042-9007.2004.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different intensities of regular donor plasmapheresis on humoral and cellular immunity, red cell and iron metabolism, and cardiovascular risk markers

Abstract: Regular donor plasmapheresis of up to 45 l of plasma per year appears to be as safe as more moderate plasmapheresis programmes, with respect to the parameters analysed in this study. Individuals donating under these conditions did not develop impaired humoral and cellular immunity, iron store depletion, or increased cardiovascular risk with regard to established biochemical risk markers. Prospective studies are required to determine more exactly than in retrospective analyses the reasons why donors withdraw fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 22 publications
5
46
0
Order By: Relevance
“…Studies have shown that weekly plasma donors may experience declines in total IgG, IgA, and IgM concentrations during the initial 4 to 6 months of serial plasmapheresis, with subsequent stabilization (8,11). Considerable individual variability exists, however (3), and no significant impact on humoral and cellular immunity has been documented (43). We observed a small but consistent and statistically significant reduction in total IgG and IgG to PA antibody levels during the period after initial plasmapheresis in this study cohort.…”
Section: Discussionsupporting
confidence: 60%
“…Studies have shown that weekly plasma donors may experience declines in total IgG, IgA, and IgM concentrations during the initial 4 to 6 months of serial plasmapheresis, with subsequent stabilization (8,11). Considerable individual variability exists, however (3), and no significant impact on humoral and cellular immunity has been documented (43). We observed a small but consistent and statistically significant reduction in total IgG and IgG to PA antibody levels during the period after initial plasmapheresis in this study cohort.…”
Section: Discussionsupporting
confidence: 60%
“…When compared to nondonors, plasma donors had lower levels of total protein, albumin and Immunoglobulin G [21], although the plasma donors evidently did not suffer from any consequence of these lower levels. In a prospective study of 3783 plasma donors, sixteen per cent of donors dropped out when Immunoglobulin G, total serum protein or hemoglobin levels fell below threshold values [22].…”
Section: Discussionmentioning
confidence: 82%
“…Plasma can be derived from whole blood donations, by separating it from the other blood components, as well as by plasmapheresis. Plasmapheresis provides the opportunity to harvest a large amount of plasma in one donation procedure (up to 650 mL compared to 250 mL in whole blood donations), while at the same time returning red blood cells (RBCs) to the donor . This procedure allows plasmapheresis donors to donate more frequently than is possible for whole blood donors, since the human body replenishes plasma quicker than it does RBCs.…”
Section: Research Into Donation Motivation Among Plasma Donorsmentioning
confidence: 99%